Why "American Patients First" is likely to raise drug prices outside of the United States. Issue 1 (1st January 2019) - Dabbous, Monique; Milea, Cyprien; Simoens, Steven; François, Clement; Dussart, Claude; Chachoua, Lylia; Borissov, Borislav; Toumi, Mondher
ABSTRACT: Background : The Trump administration's 'American Patients First' blueprint proposes to reduce drug prices in the USA by increasing drug prices abroad, ex USA. The possibility of the Trump administration to raise drug prices ex USA through legal action via the WTO and bilateral negotiations with foreign trade partners was reviewed. Methods : A literature review was conducted through PUBMED, EMBASE, Media and grey literature to consolidate publications of the Trump administrations' policies and strategies towards foreign countries and drug prices. Results : The Trump administration has withdrawn from and halted major multilateral agreements including the TPP, Paris Agreement, TTIP, UNESCO, NAFTA (now USMCA), and NATO. The Trump administration has been successful in bilateral negotiations for pharmaceuticals' pricing, as seen with Japan, South Korea, Germany, and Mexico and Canada. Conclusion : The objective of raising prices abroad is attainable. Action through the WTO is unlikely, due to its nondiscriminatory principle. Bilateral trade negotiation have proven more promising. In this bilateral framework, financial security and military protection are strong assets for the USA to levy higher drug prices abroad. Although raising drug prices ex USA is possible, further questions as to whether this will directly translate into lower drug prices for American patients are raised.